Academic-Family Integration: How Do Men and Women in Distance Education and Residential Doctoral Programs Integrate Their Degree and Family? - Rockinson-Szapkiw, Amanda; Herring Watson, Jessica (Online Learning, 2020)
Multivariate statistical analyses were used to determine if differences existed between how men and women enrolled in distance education and residential doctorate of education programs in the United States managed and negotiated their family and academic lives. Results provided evidence that distance education students (n = 106) reported having lower academic-family satisfaction and functioning, more interference between the academic and family domains, and more impermeable boundaries between the domains than their residential peers (n = 71). Moreover, women (n = 126) in comparison to men (n = 51) reported poorer academic-family balance and the desire to set more rigid boundaries between their academic and family domains.